2010
DOI: 10.1210/en.2009-0865
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Actions of Tumor Necrosis Factor α Provide the Thermogenic Core for the Wastage Syndrome in Cachexia

Abstract: TNFalpha is an important mediator of catabolism in cachexia. Most of its effects have been characterized in peripheral tissues, such as skeletal muscle and fat. However, by acting directly in the hypothalamus, TNFalpha can activate thermogenesis and modulate food intake. Here we show that high concentration TNFalpha in the hypothalamus leads to increased O(2) consumption/CO(2) production, increased body temperature, and reduced caloric intake, resulting in loss of body mass. Most of the thermogenic response is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 40 publications
(49 reference statements)
3
65
0
3
Order By: Relevance
“…4A). Previous studies have suggested brown adipose thermogenesis is associated with wasting in later stages of cachexia 19,20,35 which would explain increased expression of genes related to lipid uptake and utilization in iBAT. mRNA expression of the key kinase (p38a MAPK), transcriptional co-activators [peroxisome proliferator activated receptor gamma coactivator 1a (PGC1a), PR domain zinc finger protein 16 (PRDM16)], activating enzyme [Type II iodothyronine deiodinase (DIO2)] and uncoupling protein [uncoupling protein 1 (UCP1)] contributing to thermogenic capacity were significantly increased in Tumor mice compared to Pairfed mice but were no different than the No Tumor group with the exception of DIO2 (Fig.…”
Section: Colon-26 Carcinoma Increases Markers Of Fatty Acid Oxidationmentioning
confidence: 96%
See 1 more Smart Citation
“…4A). Previous studies have suggested brown adipose thermogenesis is associated with wasting in later stages of cachexia 19,20,35 which would explain increased expression of genes related to lipid uptake and utilization in iBAT. mRNA expression of the key kinase (p38a MAPK), transcriptional co-activators [peroxisome proliferator activated receptor gamma coactivator 1a (PGC1a), PR domain zinc finger protein 16 (PRDM16)], activating enzyme [Type II iodothyronine deiodinase (DIO2)] and uncoupling protein [uncoupling protein 1 (UCP1)] contributing to thermogenic capacity were significantly increased in Tumor mice compared to Pairfed mice but were no different than the No Tumor group with the exception of DIO2 (Fig.…”
Section: Colon-26 Carcinoma Increases Markers Of Fatty Acid Oxidationmentioning
confidence: 96%
“…Indeed, clinical studies have reported elevated rates of whole body fatty acid oxidation in weight losing (10% of initial body weight) cancer patients. 12,17,18 Studies of cachexia in rodents suggest activation of thermogenesis (i.e., increased mitochondrial uncoupling of oxidative phosphorylation and elevated fatty acid b-oxidation) in brown adipose tissue 19,20 may contribute to elevated whole body lipid utilization in cachexia, at least in later stages of cachexia. 20 Additionally, recent studies in healthy rodents and human adipocytes have linked stimulation of lipolysis in white adipose tissue with increased fatty acid oxidation 21,22 and uncoupling 21,23,24 in white adipose depots.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, cytokines were shown to increase the metabolic rate through activation of thermogenesis, inhibit adipocyte and skeletal myocyte differentiation, and reduce food intake (Guttridge et al 2000;Li et al 2002;Ruan et al 2002;Arruda et al 2010). However, weight loss in cancer patients cannot be attributed solely to decreased food intake, since dietary supplements fail to reverse cachexia (Bruera and Sweeney 2002).…”
Section: Cancer Cachexia Is An Energy Balance Disorder Linked To Inflmentioning
confidence: 99%
“…For instance, treatment with the gastrointestinal hormone ghrelin inhibits the central melanocortin system and reduces hypothalamic inflammation, resulting in weight gain and increased lean body mass in tumor-implanted rats (DeBoer et al 2007). The central mechanisms responsible for cytokine-induced body weight loss include reduction of food intake and increased metabolic rate through activation of thermogenesis (Li et al 2002;Arruda et al 2010). Less is known on the role of the hypothalamus in the pathogenesis of endocrine dysregulation observed in an organism affected by cancer, although a potential contribution of the hypothalamic-pituitary-adrenal axis is suspected.…”
Section: Endocrine Routes To Cancer Cachexiamentioning
confidence: 99%
“…The POMC/CART anorexigenic pathway activates the sympathetic nervous system and leads to the induction of mitochondrial uncoupling proteins, including UCP-1 and UCP-2 [47,48]. By dissipating the proton gradient generated during respiration across the inner mitochondrial membrane and uncoupling respiration from ATP synthesis, UCP-1 and UCP-2 result in thermogenesis and energy expenditure in brown adipose tissue (BAT) [47,48]. Increases in BAT thermogenesis have been associated with a cachectic state in both humans and experimental animals [49,50].…”
mentioning
confidence: 99%